2023
DOI: 10.1037/cns0000325
|View full text |Cite
|
Sign up to set email alerts
|

Thought characteristics in patients with severe health anxiety: A comparison with obsessive–compulsive disorder and healthy controls.

Abstract: Previous studies on health anxiety have primarily focused on general aspects of thought characteristics proposed to be central to the disorder, whereas the importance of disorderspecific thought content is often stressed in the literature. The present study examines general as well as disorder-specific aspects of several thought characteristics in 32 patients with severe health anxiety, a clinical control group of 33 patients with obsessivecompulsive disorder, and 32 healthy control participants. Both patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, social anxiety symptoms were significant positive predictors of the “Communication and miscommunication” topic (e.g., “question”, “ask”, “teacher”, “class”), and general anxiety symptoms were significant positive predictors of the “Conversations” topic (e.g., “someone”, “conversation”, “say”, “person”). These findings support the idea that there is indeed disorder-specific content in recurrent IAMs 6 , 16 , and that recurrent IAMs containing certain types of content are more likely to reflect psychopathology than other types of content 5 , 19 . In fact, we replicated a significant positive relationship between use of the “Assaults and abuse” topic and depression symptoms 19 , 56 , but with a much larger sample size and in a nonclinical sample.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, social anxiety symptoms were significant positive predictors of the “Communication and miscommunication” topic (e.g., “question”, “ask”, “teacher”, “class”), and general anxiety symptoms were significant positive predictors of the “Conversations” topic (e.g., “someone”, “conversation”, “say”, “person”). These findings support the idea that there is indeed disorder-specific content in recurrent IAMs 6 , 16 , and that recurrent IAMs containing certain types of content are more likely to reflect psychopathology than other types of content 5 , 19 . In fact, we replicated a significant positive relationship between use of the “Assaults and abuse” topic and depression symptoms 19 , 56 , but with a much larger sample size and in a nonclinical sample.…”
Section: Discussionsupporting
confidence: 79%
“…Past content analyses of autobiographical memories have been fruitful at describing the events that participants remember, revealing common topics such as accidents, holidays, and interpersonal relationships 12 15 . Importantly, some suggest that content in recurrent IAMs might change as a function of mental health status, and could even provide insights into how recurrent IAMs might diverge across different disorders 5 , 6 , 16 18 . In other words, researchers have hypothesized that content in AMs (especially recurrent IAMs) differs between (1) those experiencing high versus low levels of psychopathology, as well as between (2) those with different mental health disorders (disorder-specific content).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that individuals with OCD performed similarly to healthy controls in semantic memory (39). Some others have shown poor performance in semantic memory in OCD patients compared with healthy controls (40). Moreover, researchers found that patients with OCD did not have difficulty accessing parts of their autobiographic memory unless their illness was comorbid with depressive disorder (39).…”
Section: Discussionmentioning
confidence: 99%
“…All participants agreed to an informed consent form explaining the nature of the study, as well as issues relating to confidentiality and withdrawal. The main measures presented in this article are non‐overlapping with previous publications from this study (Gehrt, Frostholm, Obermann & Berntsen, 2020a; Gehrt, Frostholm, Pallesen et al ., 2020b; Gehrt et al ., 2022). 2…”
Section: Methodsmentioning
confidence: 99%